2016
DOI: 10.1017/dsj.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Balancing design freedom and brand recognition in the evolution of automotive brand styling

Abstract: Designers faced with the task of developing a new product model of a brand must balance several considerations. The design must be novel and express attributes important to the customers, while also recognizable as a representative of the brand. This balancing is left to the intuition of the designers, who must anticipate how customers will perceive the new design. Oftentimes, the design freedom used to meet a product attribute can compromise the recognition of the product as a member of the brand. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The motivation for this work was developed in part from working with practicing designers in the automotive industry and recognizing the necessity of a design representation that can morph between various brands and body types, yet realistic enough to convey sufficient meaning to designers [39]. This representation is not limited to brand studies.…”
Section: Resultsmentioning
confidence: 99%
“…The motivation for this work was developed in part from working with practicing designers in the automotive industry and recognizing the necessity of a design representation that can morph between various brands and body types, yet realistic enough to convey sufficient meaning to designers [39]. This representation is not limited to brand studies.…”
Section: Resultsmentioning
confidence: 99%
“…Identification and evaluation of attributes mapped to PQ are ongoing challenges in design research and industry (Yumer et al 2015;Burnap et al 2016;Stylidis et al 2016;Ma et al 2017;Lin & Tseng 2018). Designing a new generation of a product is an additional challenge when we aim to maintain the balance between novelty and perceived quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown how emotions drive human judgement and influence daily actions and decisions (Fukuda, 2017). In a similar vein, products should possess a tonality that is developed through a strong brand identity (Burnap et al, 2016;Kapferer, 2011). This brand identity needs to evoke a strong emotional reaction in consumers in order for it to sustain a loyal customer base.…”
Section: Introductionmentioning
confidence: 99%